Gold Compounds and the Anticancer Immune Response - Zhou, Ling; Liu, Huiguo; Liu, Kui; Wei, Shuang (Frontiers in Pharmacology, 2021)
Gold compounds are not only well-explored for cytotoxic effects on tumors, but are also known to interact with the cancer immune system. The immune system deploys innate and adaptive mechanisms to protect against pathogens and prevent malignant transformation. The combined action of gold compounds with the activated immune system has shown promising results in cancer therapy through in vivo and in vitro experiments. Gold compounds are known to induce innate immune responses; however, these responses may contribute to adaptive immune responses. Gold compounds play the role of a major hapten that acts synergistically in innate immunity. Gold compounds support cancer cell antigenicity and promote anti-tumor immune response by inducing the release of CRT, ATP, HMGB1, HSP, and NKG2D to enhance immunogenicity. Gold compounds affect various immune cells (including suppressor regulatory T cells), inhibit myeloid derived suppressor cells, and enhance the function and number of dendritic cells. Gold nanoparticles (AuNPs) have potential for improving the effect of immunotherapy and reducing the toxicity and side effects of the treatment process. Thus, AuNPs provide an ideal opportunity for exploring the combination of anticancer gold compounds and immunotherapeutic interventions.